Trust me, I am famous: legitimating attractive celebrities as credible endorsers for charitable organisations - Leclercq, Thomas; Denis, Etienne; Hoornaert, Steven (Journal of marketing management, 2024)
Non-profit organisations are increasingly collaborating with celebrities to increase charitable donations. Consequently, choosing the right endorser to promote charitable giving is central to the communication strategy. The present research investigates how the attractiveness and credibility of celebrities, as well as cause-endorser matchup and meaning transfer, influence people's donations. This research provides evidence of serial and parallel mediation effects by measuring and manipulating the four constructs in four separate studies. We demonstrate that credibility mediates the effect of attractiveness on generosity. Additionally, we highlight two legitimation pathways to explain how attractive endorsers become perceived as more credible cause promoters. This study provides a comprehensive model that illustrates, through an affective-cognitive-conative sequence, how attractiveness, congruence and meaning, and then credibility leads to charitable donations. Accordingly, we provide non-profit organisations with concrete and actionable recommendations for selecting celebrity endorsers.